Meningkatkan Hasil Belajar Peserta Didik dengan Model Problem Based Learning (PBL) Menggunakan Kuis Interaktif Mata Pelajaran IPAS Kelas VI SD Negeri 101771 Tembung - Fadila, Sindi; Fitriah, Fita; Nurhafni, Nurhafni; Mariana, Mariana (Lembaga Intelektual Muda (LIM) Maluku, 2024)
This research began with the learning conditions that occurred at SD Negeri 101771 Tembung which requires students to be responsible for their learning outcomes, with learning that is always monotonous to package books, new innovations are needed in carrying out creative learning with a problem-based learning model. This research aims to improve student learning outcomes through technology-based interactive quiz media, namely using a Wordwall application with a based learning model. This research was carried out in class VI A SD Negeri 101771 Tembung which was carried out in August 2024 with a research object of 32 students. The research was carried out with as many as 2 (two) cycles and 1 (one) cycle consisting of 1 (one) meeting. The results of the study concluded that learning with the problem-based learning method assisted by technology-based interactive quizzes has a positive impact on improving student learning outcomes, characterized by the completeness of student learning in the second cycle. This increase is due to students' interest in using interactive quiz media and raising their sense of competition in achieving maximum learning outcomes. The application of this quiz method can increase students' motivation and enthusiasm for learning which has an impact on improving student learning outcomes.